Peremajaan Etika Keutamaan Aristoteles - Yohanes Theo (IKIP Budi Utomo Malang, 2021)
Contemporary philosophy is known for its nuances of “the breakdown of the great narratives.” The thinkers of this era rejected ontotheology. An idea about the most basic and the highest in the discourse of logos. In other words, the contemporary era leads us to the nihilism, there is no moral values anymore, thereby rejecting ethics. However, Alasdair MacIntyre tried to dispel this notion byx rejuvenating a great ethical understanding of Aristotle, which he believes still has relevance for today's conditions. Maclntyre discusses three human characteristics that need to be used as a framework for understanding humans. The three understandings are practice, the characteristics of which must be carried out in the form of cooperation, contain internal values, have high standards, and can be expanded. Narrative order of a single human life, meaning the unity of a person’s life that shapes his life story and makes the activities he does throughout his life meaningful. The unity of the narrative does not causes fragmentation or detached phases without connection to one another in the conditions of modern enlightened society. Moral tradition, that everyone finds himself as part of a history. The tradition that Maclntyre refers to is not just a legacy of a dead past, but a tradition that is continuously lived through debate and discourse. Maclntyre pays attention to the qualities of the human person who want to be better. This self-quality is based on the narratives and traditions of each community.